2014
DOI: 10.4269/ajtmh.12-0697
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of HIV/AIDS Health Centers and Effect of Community-Based Health Insurance and Performance-Based Financing on HIV/AIDS Service Delivery in Rwanda

Abstract: This study evaluates the efficiency of rural health centers in Rwanda in delivering the three key human immunodeficiency virus/acquired immunodeficiency syndrome services: antiretroviral treatment, prevention of mother-to-child transmission, and voluntary counseling and testing using data envelopment analysis, and assesses the impact of community-based health insurance (CBHI) and performance-based financing on improving the delivery of the three services. Results show that health centers average efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…In a 2012 evaluation of Rwanda mutuelles by Lu and colleagues, the use of curative care consultations among ill children with mutuelles insurance was double the rate among those without insurance [ 20 ]. This reinforces similar findings of increased service use among the insured in Rwanda [ 21 23 ]. Interactions between insurance and PBF and insurance and wealth quintiles were tested but not included due to insignificance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a 2012 evaluation of Rwanda mutuelles by Lu and colleagues, the use of curative care consultations among ill children with mutuelles insurance was double the rate among those without insurance [ 20 ]. This reinforces similar findings of increased service use among the insured in Rwanda [ 21 23 ]. Interactions between insurance and PBF and insurance and wealth quintiles were tested but not included due to insignificance.…”
Section: Discussionsupporting
confidence: 90%
“…Interactions between insurance and PBF and insurance and wealth quintiles were tested but not included due to insignificance. Disentangling the effects of PBF from the rise of mutuelles is a difficult but promising area for future study [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abstracts and, where necessary, full text of 352 articles was examined by both reviewers. Of these, 157 were included in the final analysis [ 15 – 171 ]. Eighty-eight percent of included interventions took place across sub-Saharan Africa (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…During this systematic review several PBF evaluations were identified that were excluded because events without a denominator were reported. For example, rather than reporting coverage, the number of units of service administered in PBF facilities compared to non-PBF facilities were reported in some studies [54, 55]. Since the number of people eligible for these services may be higher in PBF facilities versus non-PBF facilities, or vice versa, it is difficult to draw any conclusion from these data.…”
Section: Discussionmentioning
confidence: 99%